Os três níveis da solução de problemas - SILVA JUNIOR, Arnaldo Oliveira (2019)
This work aims to present the problem solving from the action of the resolver in three levels called strategies, tactics and tools differentiating each one of them through classic concepts and examples. In this answer, strategies are elements that guide the first contact with the problem as well as its approach in general. While the tactics are mathematical results applied in overcoming obstacles that arise during resolution. The tools are instruments for the more specific situations of resolution. Finally, this paper presents a series of applications with problems in several areas of mathematics, aiming at identifying the elements that characterize each level of performance, demonstrating the effectiveness of problem solving from this perspective, thus offering a new point of view for the discussions on the subject.